Legal Protection of Our Guarantee Object Owners After Low Limit Value - Fatimah Zahra; Habib Adjie (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
writing of this journal aims to be able to know, analyze and understand about legal protection to the owner of the collateral object for the implementation of the auction with a low limit value. The legal analysis in this journal is focused on being able to find out the protection and legal remedies that can be carried out by the debtor or the owner of the collateral object if the determination of the results of the auction is conducted with a limit value too low than the market value so that it can be used as consideration in analyzing that there is an act against the law . Based on the research it can be seen that the low limit value can be one of the elements of the cancellation of the auction because of consideration of the actions that have been regulated by the legislation that can cause losses, errors, if it is done in accordance with the seller so that it can cause harm to other party. The injured party is the debtor or the owner of the collateral object. Therefore, the determination of auction results below the limit value can be one of the reasons for canceling the auction so that it can protect the owner of the collateral object from loss.